2004
DOI: 10.1111/j.1523-1755.2004.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial juvenile hyperuricemic nephropathy: Detection of mutations in the uromodulin gene in five Japanese families

Abstract: Our results gave an evidence for the mutation of the UMOD gene in the majority of Japanese families with FJHN. Genetic heterogeneity of FJHN was also confirmed. Genetic testing is necessary for definite diagnosis in some cases especially in the young generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Hart et al [2] first identified that the mutation of the uromodulin (UMOD) gene is responsible for FJHN. FJHN is genetically heterogeneous and mostly caused by mutations in the UMOD gene located on chromosome 16p12.3-p13.11 [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Hart et al [2] first identified that the mutation of the uromodulin (UMOD) gene is responsible for FJHN. FJHN is genetically heterogeneous and mostly caused by mutations in the UMOD gene located on chromosome 16p12.3-p13.11 [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…8 We have analyzed the 81 markers on chromosome 16p that are used in the analysis by Kudo et al 9 The pedigree consists of 65 individuals, but only 58 descendants are analyzed because seven ancestors have no effect on the maximization of the likelihood since their marker genotypes are not available (NA). We also changed the affected status of IV-21 to non-affected since Kudo et al 9 reported that it is a phenocopy. We assume that the mode of inheritance is autosomal dominant with one liability class with penetrance 0, 0.95 and 0.95.…”
Section: Pedigree Datamentioning
confidence: 99%
“…A syndrome of familial juvenile hyperuricemic nephropathy (FJHN [MIM 162000]) is an autosomal dominant disorder in which abnormal renal tubular excretion of uric acid and gout are associated with the late development of interstitial nephritis and progressive renal failure [44,45,46].…”
Section: Genetic Transmission Is Autosomal Dominantmentioning
confidence: 99%
“…An interesting new mechanism for hyperuricemia has been recently discovered in FJHN [45,46]. It is to pathologic findings in FJHN raised similarities with autosomal dominant medullary cystic kidney disease (MCKD [MIM 174000]).…”
Section: Biochemical and Molecular Featuresmentioning
confidence: 99%
See 1 more Smart Citation